2012
DOI: 10.1111/ctr.12000
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic seizures in patients following allogeneic hematopoietic stem cell transplantation: a retrospective analysis of incidence, risk factors, and survival rates

Abstract: The incidence of epileptic seizures among allogeneic hematopoietic stem cell transplant (allo-HSCT) patients has been poorly described. No report has systematically studied epilepsy's possible causes, risk factors, and effect on prognosis among allo-HSCT patients. We retrospectively examined data from 1461 patients who underwent allo-HSCT within the past 6.5 yr at the Institute of Hematology and People's Hospital, Peking University. The cumulative incidence of all epileptic seizure complications was 7.1%. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 17 publications
4
52
2
Order By: Relevance
“…There appears to be no close correlation between pre-transplant disease or symptoms and etiology of CNS complications. One-year survival declined significantly in patients who experienced seizures (57% versus 75%) [69]. Risk factors for seizures included young age, allogeneic transplant, acute GVHD and hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be no close correlation between pre-transplant disease or symptoms and etiology of CNS complications. One-year survival declined significantly in patients who experienced seizures (57% versus 75%) [69]. Risk factors for seizures included young age, allogeneic transplant, acute GVHD and hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…All patients who developed IMNs had underlying hematologic malignancies. Other risk factors associated with IMNs include unrelated donor, infection, and GVHD [83,84]. Although dysregulated immune reconstitution has been implicated, early relapse of primary hematologic malignancy was associated with IMN in 1 retrospective analysis, suggesting that paraneoplastic antibody production is implicated [80].…”
Section: Immune-mediated Neuropathiesmentioning
confidence: 99%
“…Peripheral nervous system IMNs include acute and chronic inflammatory demyelinating polyneuropathy, autonomic neuropathies, plexopathies, mononeuropathies, and polyradiculopathies, such as Guillain-Barré syndrome [80][81][82]. IMN after HSCT is uncommon, with incidence ranging from .36% to 3.6% [75,80,83].…”
Section: Immune-mediated Neuropathiesmentioning
confidence: 99%
“…Drake et al [37] and Wells et al [38] found that seizures may be related to low blood glucose or to a drop in blood osmotic pressure and serum sodium but that hypomagnesemia or hypocalcemia may not increase the risk of developing seizures in renal transplant recipients. In addition, the literature reported that the etiology for most seizures involves hyponatremia combined with hypokalemia in recipients of hematopoietic stem cell transplantation [39].…”
Section: Metabolic Disordersmentioning
confidence: 99%
“…Listeria aspergillus, Cryptococcus neoformans and aspergillus fumigatus are the main pathogens causing central nervous system infections [40]. Central nervous system infections, particularly viral or fungal infections, can cause brain damage and induce seizures [39,[41][42][43]. In addition, seizures may also be related to the inflammatory response, and there is literature reported that IL-1beta can break the balance between glutamate and GABA [44].…”
Section: Infectionmentioning
confidence: 99%